Bioengineered transplantable porcine livers with re-endothelialized vasculature. (February 2015) - Ko, In Kap; Peng, Li; Peloso, Andrea; Smith, Charesa J.; Dhal, Abritee; Deegan, Daniel B.; Zimmerman, Cindy; Clouse, Cara; Zhao, Weixin; Shupe, Thomas D.; Soker, Shay; Yoo, James J.; et al.
Abstract: Donor shortage remains a continued challenge in liver transplantation. Recent advances in tissue engineering have provided the possibility of creating functional liver tissues as an alternative to donor organ transplantation. Small bioengineered liver constructs have been developed, however a major challenge in achieving functional bioengineered liver in vivo is the establishment of a functional vasculature within the scaffolds. Our overall goal is to bioengineer intact livers, suitable for transplantation, using acellular porcine liver scaffolds. We developed an effective method for reestablishing the vascular network within decellularized liver scaffolds by conjugating anti-endothelial cell antibodies to maximize coverage of the vessel walls with endothelial cells. This procedure resulted in uniform endothelial attachment throughout the liver vasculature extending to the capillary bed of the liver scaffold and greatly reduced platelet adhesion upon blood perfusion in vitro . The re-endothelialized livers, when transplanted to recipient pigs, were able to withstand physiological blood flow and maintained for up to 24 h. This study demonstrates, for the first time, that vascularized bioengineered livers, of clinically relevant size, can be transplanted and maintained in vivo, and represents the first step towards generating engineered livers for transplantation to patients with end-stage liver failure.